STUDENTS’ VOCABULARY ACHIEVEMENT BY USING LIST GROUP LABEL - Junaid Junaid (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2012)
The research aimed to find out the improvement of the students’ vocabulary mastery by List Group Label (LGL) at the first year students of SMP Nasional Makassar in 2011/2012 Academic Year. The researcher used a classroom action research method with the cycle I and cycle II design, where each cycle consisted of four meetings. It employed vocabulary test instrument. A number of subjects of the research were 25 students in the first year class. They consisted of 12 women and 13 men. The research took real data from the school to know the students’ vocabulary mastery. The research findings indicated that using List Group Label (LGL) could improve the students’ nouns from cycle I to cycle II, whereas in cycle I the students’ achievement in nouns was 57.70%, but after evaluation in cycle II, the students’ nouns became 73.80%. On the other hand, the students’ verbs developed too from cycle I to cycle II, wherein cycle I the students’ achievement in verbs was 57.60%, but after evaluation in cycle II, the students’ verbs became 74.60%. The findings indicated that there was the improvement in the students’ vocabulary mastery from cycle I to cycle II, wherein cycle I the students’ vocabulary mastery was 57.70%, but after evaluation in cycle II, the students’ vocabulary mastery became 74.20%. While the standard targeted achievement was 62%.Keywords: Vocabulary, Achievement, List Group Label.